Surgical retention for immediate obturator in maxillectomy patients - Rajendran Appadurai; D Lingeshwar; B Dilshad; S Maria (Wolters Kluwer Medknow Publications, 2019)
Total maxillectomy for patients with malignant lesions will often incapacitate the patient both functionally and aesthetically. An immediate surgical obturator prosthesis would be of utmost importance for patients in these critical situations to aid in deglutition, phonetics, respiration and effectively avoiding various post-surgical complications. This article emphasizes on utilizing circum-zygomatic wiring for retention of the immediate surgical obturator in cases of total maxillectomy or edentulous patients.